Relationship between socio-economic backgrounds and secondary school students’ achievements and self-beliefs: A comparative study of Finland and Singapore - Lim, Ai Hong (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis explores whether the achievement and self-beliefs of secondary school students are related to their socio-economic background in two different national contexts, Finland and Singapore. Both countries have a predominantly public school system and provide a high standard of national education, as evident in the strong PISA performances. However, high stratification is present in Singapore’s education system, with students being selected into different academic streams while such differentiation is not present in Finland’s comprehensive system. This comparative study uses 2012 PISA data. The sample consists of 15-year-old Finnish (n = 8829) and Singaporean (n = 5546) secondary school students – from 311 and 172 schools sampled in Finland and Singapore respectively – who participated in 2012 PISA. The PISA Index of economic, social and cultural status (ESCS) was used as a measure of socio-economic background while mathematics test-score plausible values were used as a measure of achievement in this study. Using students’ responses to 25 scale-items of the questionnaire, self-beliefs were measured through four dimensions: ‘perceived self-efficacy’, ‘perceived self-concept’, ‘perceived controllability (internal)’ and ‘perceived controllability (external)’. In this study, quantitative analysis was conducted. Besides principal components analysis (PCA) of the questionnaire scale-items, the relationships between the variables socio-economic background, achievement and self-beliefs were investigated using one-way analysis of variance (ANOVA) and multiple regression analysis. In both countries, a strong relationship between socio-economic background and achievement was found, with socio-economic background found to predict achievement. Secondly, socio-economic background was found to be related to self-efficacy and, to a smaller extent, self-concept in both countries. In Singapore, the relationship between socio-economic background and achievement as well as that between background and self-efficacy beliefs, and that between self-efficacy and achievement were stronger than in Finland. However, self-concept was not found to predict achievement in Singapore although it was a strong predictor of achievement in Finland. Thirdly, perceived controllability was not found to be strongly related to socio-economic background for Finnish students. This was also the case for internal controllability in Singapore but not for external controllability. Lastly, while controllability contributed to the prediction of achievement, but to smaller extents than socio-economic background and self-efficacy, internal controllability beliefs seemed to counteract external controllability.